Tourism WEBGIS Processing Training To Help POKDARWIS In Update Tourism Data Digitally - Sri Mariya; Widya Prarikeslan; Triyatno Triyatno; Pasaribu Pasaribu; Vivi Angraini; Dion Lovani; Viki Aulia Pratama (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Tourism activities are not supported by technology so that tourism potential is not optimally utilized. The platform designed for tourism in Pulai Anak Air is WebGIS Taourism. The program is carried out by involving the Pulai Anak Air Village Government, POKDARWIS, Homestay Managers, and local MSMEs. The method used is Focus Group Discussion (FGD) and training with WebGIS Tourism data management practices and updates that involve participants directly. The number of participants is 10 people who are representatives of each Institution. The results achieved are that training participants are able to update data in real time according to the needs of tourism, homestays, and MSMEs. Based on the evaluation conducted by the Community Service Team of training participants, it was found that 6 out of 10 participants were able to manage WebGIS Tourism independently. In addition, the sustainability of the program carried out by the team is in the form of regular mentoring related to website management.